Synthesis and evaluation of nickel cobalt ferrite magnetic ceramics employing two alternative routes - Camargo, Javier Eduardo (2021)
Ni0.5Co0.5Fe2O4 (NCF) powders were obtained employing two alternative synthesis routes: solid-state reaction, and Pechini´s methods. The ceramic powders were pressed and sintered in the temperature range of 1100 ºC to 1250 ºC. Microstructural and structural properties were evaluated by SEM, XRD, and Raman spectroscopy. Magnetic hysteresis loops of sintered samples were also recorded. A secondary phase was observed in samples synthesized by Pechini´s method, whereas samples obtained by the solid-state reaction method, with the mechanochemical activation of the reagents, only produced the spinel-structure. Magnetic properties of samples obtained by the solid-state method displayed higher magnetic saturations and lower coercive fields than those obtained from the from Pechini´s method.